2016
DOI: 10.1007/s11676-016-0281-7
|View full text |Cite
|
Sign up to set email alerts
|

Applications and roles of the CRISPR system in genome editing of plants

Abstract: Genome editing is a valuable tool to target specific DNA sequences for mutagenesis in the genomes of microbes, plants, and animals. Although different genome editing technologies are available, the clustered regularly interspaced short palindromic repeats/Cas9 (CRISPR/ Cas9) system, which utilizes engineered endonucleases to generate a double-stranded DNA break (DSB) in the target DNA region and subsequently stimulates site-specific mutagenesis through DNA repair machineries, is emerging as a powerful genome e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 79 publications
0
3
0
2
Order By: Relevance
“…The single-plant yield directly reflects the response of a maize variety to planting density while the population yield is the result of combined action of the potential productivity of maize and the response to planting density. For plant breeding and to identify density resistance, both factors should be combined to determine whether a maize variety is resistant to high density 17 , 34 . In this test, the population yields and the single-plant yields are combined to consider the density resistance of a maize variety, and the results are considered more accurate and feasible.…”
Section: Discussionmentioning
confidence: 99%
“…The single-plant yield directly reflects the response of a maize variety to planting density while the population yield is the result of combined action of the potential productivity of maize and the response to planting density. For plant breeding and to identify density resistance, both factors should be combined to determine whether a maize variety is resistant to high density 17 , 34 . In this test, the population yields and the single-plant yields are combined to consider the density resistance of a maize variety, and the results are considered more accurate and feasible.…”
Section: Discussionmentioning
confidence: 99%
“…Tang et al (2017) [14] reported that gene Additionally, editing can be a very helpful tool for assessing the phenotype of alleles found in germplasm, wild populations of germplasm that has been acclimated to a certain environment, or figuring out the purpose of synthetic alleles. Haque et al (2018) [8] concluded that the combination of advances in genomic analysis and gene editing should allow a new phase of plant improvement based upon design and building of genotypes to target specific objectives such as adaptation of crops to new field or protected environments.…”
Section: Genetic Improvement Technologymentioning
confidence: 99%
“…Esta técnica se basa en el uso de nucleasas que inducen ruptura de la doble cadena (DSB, por sus siglas en inglés) de ADN en sitios específicos del genoma, y permite manipular prácticamente cualquier gen al generar deleciones, inserciones o cambios en las secuencias de ADN. Las primeras aproximaciones desarrolladas se basaban en el uso de sistemas de proteínas con afinidades específicas al ADN, como por ejemplo las nucleasas con dedos de zinc (ZFNs, por sus siglas en inglés) y nucleasas efectoras tipo activador de transcripción (TALENs, por sus siglas en inglés) (Gaj et al, 2013;Sander y Joung, 2014;Tang y Tang, 2017).…”
Section: Edición Génica En Cultivos De Origen Neotropicalunclassified
“…Este método, a diferencia de las ZFN y TALENs, permite tener más de una secuencia objetivo al coexpresar la proteína Cas9 con múltiples ARN guía (ARNg) de forma simultánea (Sternberg y Doudna, 2015). Mediante la edición génica es teóricamente posible realizar cambios tendientes a mejorar rendimiento y calidad de los cultivos, así como también incrementar la resistencia a enfermedades y virus en los mismos (Gaj et al, 2013;Sander y Joung, 2014;Tang y Tang, 2017).…”
Section: Edición Génica En Cultivos De Origen Neotropicalunclassified